FACTORS HINDERING THE HERITAGE DESTINATION PROMOTION IN MALAYSIAN CONTEXT - SUJANA ADAPA (ASEAN Journal on Hospitality and Tourism, 2008)
The present research empirically investigates the preferences of the respondents currently residing in Malaysia towards the promotion of heritage destinations in Kuala Lumpur. The present study makes an attempt to identify the key determinant factors that are actually hindering the heritage destination promotion in Malaysian context. For the purpose of the research, the attractions in Kuala Lumpur are segmented as Heritage, Architectural, Natural and Amusement landmarks. Data has been collected from a self-administered questionnaire, returned by 100 survey participants. In accordance with thedestination competitiveness analysis and based on the preferences and attitudes expressed by the respondents towards these attractions, they are grouped as heritage and tourist destination travelers.Visitor profiles are developed depending upon their demographics such as age, income, education, occupation and marital status. Different heritage destination activities including visit to art galleries and museums, historical organizations and towns, cultural festivals etc., are studied in association with the heritage traveler site assessment. The awareness, visitation, interest, importance and satisfaction levels of the travelers to heritage sites are assessed in detail.Furthermore, motivations and barriers to visit heritage sites in conjunction with other prevailing attractions are examined. Apart from the above mentioned, respondents satisfaction, awareness and spending levels are measured with reference to the heritage travel attributes and amenities usage. Respondent's intention and preference to visit as well as revisit heritage sites in comparison with other architectural, natural and amusement landmarks are explored. The importance of information sources in promotion of heritage destinations to the travelers is presented and managerial implications are discussed. Moreover, SWOT analysis thoroughly analyzes the current market situation for heritage destination promotion in Kuala Lumpur. Avenues for further research are presented.